Diamond Surfaces with Air-Stable Negative Electron Affinity and Giant Electron Yield Enhancement - O’Donnell, Kane; Edmonds, M.; Ristein, J.; Tadich, A.; Thomsen, L.; Wu, Q.; Pakes, C.; Ley, L. (Wiley, 2013)
The presence of an air-stable negative electron affinity (NEA) on lithium-covered oxygen-terminated diamond after a thermal activation process is demonstrated. The NEA is unequivocally established by the onset of photoelectron yield at the bandgap energy of 5.5 eV. This surface exhibits a secondary electron yield enhancement by a factor of 200, compared to a surface with positive electron affinity. The surface chemistry leading to the necessary surface dipole was elucidated by core-level photoemission spectroscopy in conjunction with previous theoretical calculations. The insensitivity to the details of the deposition process opens a route to practical and robust negative-electron affinity devices based on diamond.